Unification of Strong-Weak Interactions and Possible Unified Scheme of Four-Interactions - Chang, Yi-Fang (European Journal of Applied Sciences, 2020)
First, various known unified theories of interactions in particle physics are reviewed. Next, strong and weak interactions are all short-range, which should more be unified. Except different action ranges their main character is: strong interactions are attraction each other, and weak interactions are mutual repulsion and derive decay. We propose a possible method on their unification, whose coupling constants are negative and positive, respectively. Further, we propose a figure on the unification of the four basic interactions in three-dimensional space, and search some possible tests and predictions, for example, strong-weak interactions transform each other, some waves may be produced. Finally, based on the simplest unified gauge group GL(6,C) of four-interactions, a possible form of Lagrangian is researched. Some relations and equations of different interactions are discussed.